Honey’s Ability to Counter Bacterial Infections Arises from Both Bactericidal Compounds and QS Inhibition - Wang, Rui; Starkey, Melissa; Hazan, Ronen; Rahme, Laurence (Frontiers in Microbiology, 2012)
The ability of honey to kill bacterial pathogens in vitro and quickly clear even chronic or drug-resistant infections has been demonstrated by several studies. Most current research is focused on identifying the bactericidal compounds in honey, but the action of the compounds discovered is not sufficient to explain honey’s activity. By diluting honey to sub-inhibitory levels, we were able to study its impact on bacterial behavior, and discovered that honey inhibits bacterial quorum sensing (QS). Experiments to characterize and quantify honey’s effect on the QS networks of Pseudomonas aeruginosa revealed that low concentrations of honey inhibited the expression of MvfR, las and rhl regulons, including the associated virulence factors. This research also establishes that inhibition of quorum sensing is associated with honey’s sugar content. Therefore, honey combats infections by two independent mechanisms acting in tandem: bactericidal components, which actively kill cells and disruption of QS, which weakens bacterial coordination and virulence.